Design approach for optimization of a piston ring profile considering mixed lubrication - Zhinan Zhang; Jun Liu; Youbai Xie (Friction)
Abstract To reduce the friction of a piston ring while maintaining a large oil film load-carrying capacity, an approach comprising of the inverse method and the sequential quadratic programming algorithm was proposed. The approach considers the variation of mixed lubrication and variable lubricant viscosity with temperature along the engine stroke, is developed to optimize the profile of a piston ring. A piston ring profile is represented by a polynomial function. A case study of the second piston ring shows that the proposed method can be applied for the optimization of a piston ring profile. In addition, this paper illustrates the effects of the degree of a polynomial function. The results show that the minimization of friction and maximization of oil film load-carrying capacity can be balanced simultaneously when the degree of the polynomial is 2 and 5.